Analysis and Optimation Hydrofoil Supported Catamaran (HYSUCAT) Size 25 Meter based on CFD Method - Hari Prastowo; Agoes Santoso; Andre Arya B (International Journal of Marine Engineering Innovation and Research, 2016)
In the field of transportation, ship is relatively cheap then others transportation. However, the ship still has constraints on speed and fuel consumption. Therefore, the ship has many variations of shape to achieve optimal condition. For example the body of ships with double hulls (catamaran) or three (trimaran), that using foil to make ship can have a smaller resistance to achieve optimal efficiency. The purpose of this research in order to plan the maximum foil shape which can produce high force of buoyance on the catamaran boat (25 meters) and also to determine the type of hydrofoil that produces maximum buoyance force using CFD method.